2005
DOI: 10.1183/09031936.05.00133204
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis infection in children who are contacts of immigrant tuberculosis patients

Abstract: The present study aimed to determine what proportion of children who are in close contact with immigrant tuberculosis (TB) patients are infected with Mycobacterium tuberculosis.For 1.5 yrs, 14 municipal health services in the Netherlands collected data from all non-Dutch TB patients and their contacts. Close contacts aged ,16 yrs received a tuberculin skin test (TST). A positive TST was defined as an induration of o10 mm among nonvaccinated children, and o16 mm among bacille Calmette-Guérin-vaccinated children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(33 reference statements)
1
6
2
1
Order By: Relevance
“…Previous studies have found that contacts of smearpositive index cases are more likely to be infected with TB and develop TB (15,16). Our study found no difference in the odds of TB disease between contacts of smear-negative and smearpositive index patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that contacts of smearpositive index cases are more likely to be infected with TB and develop TB (15,16). Our study found no difference in the odds of TB disease between contacts of smear-negative and smearpositive index patients.…”
Section: Discussionmentioning
confidence: 99%
“…Children who have spent a longer time (i.e. >1 month) in a high-prevalence country in close contact with the local population should be tested immediately after their return and retested after 3 months if the initial result is negative (Table 1) [44,82]. Disease has to be excluded in every child with signs of infection (e.g.…”
Section: Indications For Testingmentioning
confidence: 99%
“…in Germany, towards targeted testing for tuberculosis infection and suspension of BCG vaccination [19]. Nevertheless, tuberculosis is still regarded as a serious infection, particularly with the background of migration and emerging drug resistance [28,82]. The goal of preventive measures therefore remains the early diagnosis and treatment of primary tuberculosis infections.…”
Section: Introductionmentioning
confidence: 99%
“…Se recolectaron datos de todos los pacientes inmigrantes con tuberculosis y sus contactos; fueron incluidos los pacientes nacidos en los Países Bajos con padres no holandeses y también los solicitantes de asilo y otros inmigrantes. Como método de evaluación de los factores de riesgo para la infección, los niños con una prueba de sensibilidad a la tuberculina positiva y sus pacientes índices se compararon con aquellos con una tuberculina negativa, por medio de un análisis de regresión logística (21).…”
Section: Eventos Transmisiblesunclassified